Sistem Penjaminan Mutu Internal Madrasah Berdasarkan Nilai-Nilai Pesantren - Syaifullah. Syaifullah.; Tatik Swandari (THE JOER: Journal Of Education Research, 2021)
Abstract: The government implements a quality assurance system for various quality problems in Indonesia. However, this requires internal efforts of educational institutions, especially madrasas as educational institutions that focus on general science and religious knowledge as well as the preservation of pesantren values ​​in them. This article aims to study the madrasah internal quality assurance process, starting from setting quality standards, quality mapping, planning quality compliance, quality compliance, and evaluating quality compliance based on Islamic boarding school values ​​embedded in all components of the madrasa. The study was conducted at the MA Riyadlus Sholihin, Probolinggo City. This study adopts a qualitative approach through case study research. Based on data collected through interviews, observations, and document analysis. This study found that the determination of the quality standard of MA Riyadlus Sholihin refers to the SNP which is adjusted to the vision, mission and conditions of the madrasa. In quality mapping, madrasahs conduct EDM to identify strengths, weaknesses, opportunities, threats and appropriate recommendations. Quality fulfillment plans are prepared based on the results of quality mapping in the form of Madrasah Work Plans (RKM) and Madrasah Annual Work Plans (RKTM) which contain quality objectives, programs, indicators of success of the person in charge and schedule of activities as well as sources of funding and budget. Quality fulfillment is designed by the person in charge of activities by forming a team for implementing activities, technical activities, schedules and details of the budget. Evaluation of quality fulfillment is based on reports related to the implementation of activities and their results, constraints and recommendations for improvement of subsequent activities. Pesantren values ​​embedded in madrasah stakeholders have an influence on the running of SPMI.